Being, becoming, and belonging: reconceptualizing professional identity formation in medicine - Sternszus, Robert; Steinert, Yvonne; Razack, Saleem; Boudreau, J. Donald; Snell, Linda; Cruess, Richard L. (Frontiers in Medicine, 2024)
Over the last decade, there has been a drive to emphasize professional identity formation in medical education. This shift has had important and positive implications for the education of physicians. However, the increasing recognition of longstanding structural inequalities within society and the profession has highlighted how conceptualizations of professional identity formation have also had unintended harmful consequences. These include experiences of identity threat and exclusion, and the promotion of norms and values that over-emphasize the preferences of culturally dominant groups. In this paper, the authors put forth a reconceptualization of the process of professional identity formation in medicine through the elaboration of 3 schematic representations. Evolutions in the understandings of professional identity formation, as described in this paper, include re-defining socialization as an active process involving critical engagement with professional norms, emphasizing the role of agency, and recognizing the importance of belonging or exclusion on one’s sense of professional self. The authors have framed their analysis as an evidence-informed educational guide with the aim of supporting the development of identities which embrace diverse ways of being, becoming, and belonging within the profession, while simultaneously upholding the standards required for the profession to meet its obligations to patients and society.